Neurochemical Control of Rapid Stress‐Induced Changes in Brain Aromatase Activity. (21st March 2013) - Dickens, M. J.; Cornil, C. A.; Balthazart, J.
Abstract : In the male brain, the medial preoptic nucleus (POM) is known to be a critical relay for the activation of sexual behaviour, with the aromatisation of testosterone into 17β‐oestradiol (E2 ) playing a key role. Acute stress has been shown to differentially modulate the aromatase enzyme in this and other brain nuclei in a sex‐specific manner. In POM specifically, stress induces increases in aromatase activity (AA) that are both rapid and reversible. How the physiological processes initiated during an acute stress response mediate sex‐ and nuclei‐ specific changes in AA and which stress response hormones are involved remains to be determined. By examining the relative effects of corticosterone (CORT), arginine vasotocin (AVT, the avian homologue to arginine vasopressin) and corticotrophin‐releasing factor (CRF), the present study aimed to define the hormone profile regulating stress‐induced increases in AA in the POM. We found that CORT, AVT and CRF all appear to play some role in these changes in the male brain. In addition, these effects occur in a targeted manner, such that modulation of the enzyme by these hormones only occurs in the POM rather than in all aromatase‐expressing nuclei. Similarly, in the female brain, the experimental effects were restricted to the POM but only CRF was capable of inducing the stress‐like increases in AA. These data further demonstrate the high degree of specificity (nuclei‐, sex‐ and hormone‐specific effects) in this system, highlighting the complexity of the stress–aromatase link and suggesting modes through which the nongenomic modulation of this enzyme can result in targeted, rapid changes in local oestrogen concentrations.